246 Examining Melatonin-induced Changes in Uterine Blood Flow and Vaginal Temperatures in Nutrient Restricted Pregnant Heifers. (8th October 2021) - Contreras-Correa, Zully E; Messman, Riley D; Sanchez-Rodriguez, Hector; Lemley, Caleb O
Abstract: The objectives were to examine melatonin mediated changes in temporal uterine blood flow (UBF) and vaginal temperatures (VT) in 54 Brangus heifers (Fall, n = 29; Summer, n = 25) during compromised pregnancy. At d160 of gestation, heifers were assigned to 1 of 4 groups consisting of adequately fed (ADQ-CON; 100% NRC; n=13), global nutrient restricted (RES-CON; 60% NRC; n = 13), and ADQ or RES supplemented with 20 mg of melatonin (ADQ-MEL, n = 13; RES-MEL, n = 15). In the morning (0500h) and afternoon (1300h) of d220 of gestation, temperature dataloggers (Onset Computer Corporation) attached to progesterone-free CIDRs were used to record VT, while UBF was determined via Doppler ultrasonography. Data were analyzed using repeated measures of ANOVA (SAS). Significant differences were found in UBF and VT between Fall and Summer groups (P< 0.05), therefore seasons were individually analyzed. In Fall, a nutrition by treatment interaction was significant, where the RES-CON heifers exhibited reduced total UBF compared to ADQ-CON (5.67±0.68 vs. 7.97±0.54 L/min; P = 0.012). In Summer, there was not a main effect of nutrition (P = 0.390); nevertheless, the MEL heifers exhibited increased total UBF compared to the CON counterparts (8.16±0.73 vs. 6.00±0.70 L/min; P = 0.048). Moreover, there was a nutrition by treatment by time interaction in VT for Fall and Summer heifers (P < 0.0001). In Fall, all groups had decreased VT in the morning compared to the afternoon (P < 0.0001). Whereas, in Summer, VT increased for ADQ-CON, RES-CON, and ADQ-MEL from morning to afternoon (P < 0.0001), while the RES-MEL remained constant throughout the day (P = 0.649). Furthermore, during the afternoon RES-MEL heifers exhibited decreased VT compared to ADQ-CON (38.91±0.09 vs. 39.26±0.09°C, respectively; P=0.039). In summary, nutrient restriction and melatonin supplementation altered UBF in a season dependent manner. Additionally, with the VT differences observed in Summer, future studies should evaluate the potential of melatonin supplementation for mitigating heat stress in farm animals.